2014
DOI: 10.1021/jp501396a
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer at Oxide/Water Interfaces Induced by Ionizing Radiation

Abstract: International audienceThe electron transfer from oxide into water is studied in nanoparticle suspensions of various oxides (SiO2, ZnO, Al2O3, Nd2O3, Sm2O3, and Er2O3) by means of pulse and γ radiolysis. The time-resolved and steady-state investigations of the present study demonstrate independently that whatever the band gap and the electron affinity of the oxide, the electron transfer always takes place in these nanometric systems: Irradiation generates hot electrons which have enough energy to cross the semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Second, the "chemical" effect deals with interface reactions. It has been shown that water radiolysis at solid/water interfaces has a very different chemistry than in the bulk (Chelnokov et al, 2014;Schofield et al, 2016) and the NP should be studied as such. Third, now that radicals generation by NP has been assessed at a macroscopic scale, their spatiotemporal production should be investigated through simulations and experimental work, giving access to a nanodosimetry.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the "chemical" effect deals with interface reactions. It has been shown that water radiolysis at solid/water interfaces has a very different chemistry than in the bulk (Chelnokov et al, 2014;Schofield et al, 2016) and the NP should be studied as such. Third, now that radicals generation by NP has been assessed at a macroscopic scale, their spatiotemporal production should be investigated through simulations and experimental work, giving access to a nanodosimetry.…”
Section: Resultsmentioning
confidence: 99%
“…We used p-benzoquinone (PBQ) as ·O 2 -scavengers, [57][58][59][60][63][64][65] triethanolamine (TEOA) as h + scavengers, 61,62,65 and isopropanol (IPA) as ·OH scavengers. 63,66 These scavengers were added into the MO solution together with the 1D Ag@Cu 2 O core-shell hetero-nanowires before irradiation. As depicted in Figure 6, the complete inhibition of degradation of MO in the presence of TEOA suggests that photogenerated holes are the major reactive species for the photocatalytic degradation of MO.…”
Section: Resultsmentioning
confidence: 99%
“…Two previous studies have compared the behaviour of several metal oxides under gamma irradiation. Chelnokov et al (2014) measured yields of solvated electrons, relative to water, following radiolysis of concentrated metal oxide NP aqueous solutions in low oxygen conditions. Six of those NPs are in common with our study: Al 2 O 3 , SiO 2 , ZnO, Nd 2 O 3 , Sm 2 O 3 , and Er 2 O 3 (Chelnokov et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Petrik et al (2001) compared hydrogen production from adsorbed water on a wide range of 28 different element metal oxide powders (Petrik et al 2001). Chelnokov et al (2014) compared solvated electron production from six different element NPs (Chelnokov et al 2014).…”
Section: Introductionmentioning
confidence: 99%